Uso e rotação de opioides para dor crônica não oncológica - Kraychete, Durval Campos (2012)
BACKGROUND AND OBJECTIVES: Prolonged use of opioids is a possibility for chronic pain treatment. Opioids are effective for virtually all chronic non-cancer pain syndromes, but may cause dependence. The aim of this paper is to review the use and rotation of opioids in chronic non-oncologic pain. CONTENT: The use of potent opioids is controversial and not recommended as first-line drugs due to the possibility of dependence. The following topics are described: tolerance, addiction, risk factors for addiction, rotation or replacement, general administration rules, conversion tables, and tips for prescribing opioids. CONCLUSIONS: Opioids are drugs with proven efficacy for chronic non-oncologic pain, but its prescription should meet certain criteria in order to reduce the incidence of adverse effects and addiction.